2023
DOI: 10.3390/biom13060884
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle MicroRNA Patterns in Response to a Single Bout of Exercise in Females: Biomarkers for Subsequent Training Adaptation?

Abstract: microRNAs (miRs) have been proposed as a promising new class of biomarkers in the context of training adaptation. Using microarray analysis, we studied skeletal muscle miR patterns in sedentary young healthy females (n = 6) before and after a single submaximal bout of endurance exercise (‘reference training’). Subsequently, participants were subjected to a structured training program, consisting of six weeks of moderate-intensity continuous endurance training (MICT) and six weeks of high-intensity interval tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…We also found that the baseline expression of miRNAs could predict the functional response to IDE, but that more detailed evidence is lacking. The roles of MiRNA expression profiles in functional adaptation to resistance training are well described in healthy and chronic disease populations, but limited evidence exists on the effectiveness and individualisation of IDE (Davidsen et al, 2011;Kirby & McCarthy, 2013;Van Craenenbroeck et al, 2015;Ogasawara et al, 2016;Hagstrom & Denham, 2018;Domańska-Senderowska et al, 2019;Navaratnarajah et al, 2020;Robinson et al, 2020;Da Silva et al, 2021;Bell et al, 2022;de Luca Corrêa et al, 2022;Krammer et al, 2022;Telles et al, 2022;Widmann et al, 2022;Grieb et al, 2023;Kotewitsch et al, 2023;Mastrototaro & Roden, 2023;Wang et al, 2023;Xhuti et al, 2023). This implies that future studies on the roles of miRNA expression profiles in physiological response to different settings of physical activity might significantly increase effectiveness on muscle function, partially in a group of lowresponding patients.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…We also found that the baseline expression of miRNAs could predict the functional response to IDE, but that more detailed evidence is lacking. The roles of MiRNA expression profiles in functional adaptation to resistance training are well described in healthy and chronic disease populations, but limited evidence exists on the effectiveness and individualisation of IDE (Davidsen et al, 2011;Kirby & McCarthy, 2013;Van Craenenbroeck et al, 2015;Ogasawara et al, 2016;Hagstrom & Denham, 2018;Domańska-Senderowska et al, 2019;Navaratnarajah et al, 2020;Robinson et al, 2020;Da Silva et al, 2021;Bell et al, 2022;de Luca Corrêa et al, 2022;Krammer et al, 2022;Telles et al, 2022;Widmann et al, 2022;Grieb et al, 2023;Kotewitsch et al, 2023;Mastrototaro & Roden, 2023;Wang et al, 2023;Xhuti et al, 2023). This implies that future studies on the roles of miRNA expression profiles in physiological response to different settings of physical activity might significantly increase effectiveness on muscle function, partially in a group of lowresponding patients.…”
Section: Implications For Future Researchmentioning
confidence: 99%